Developments in accounting regulation: A synthesis and annotated bibliography of evidence and commentary in the 2016 academic literature. Issue 1 (April 2018) - Moehrle, S.; Kozloski, T.; Meckfessel, M.; Reynolds-Moehrle, J.; Wen, H.
ABSTRACT: In this paper key regulation-related findings and commentaries in the 2016 academic literature are synthesized in annotated form. This paper is one in a series of previously published annotated bibliographies published in this journal. Papers published in academic outlets including The Accounting Review, Journal of Accounting Research, Journal of Accounting and Economics, Contemporary Accounting Research, Accounting Horizons, The Journal of Accounting, Auditing & Finance, Journal of Accounting and Public Policy, Journal of Business, Finance & Accounting, The Journal of Financial Reporting, Auditing A Journal of Practice and Theory, and Research in Accounting Regulation were reviewed for potential inclusion. The 2016 literature featured strong regulation-related threads as follows: financial accounting regulation, analysis of individual pronouncements, SEC regulatory activity and its impact, international financial reporting standards, income tax reporting, and auditing.